2016
DOI: 10.1055/s-0036-1571428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Postoperative Outcomes Following Total Knee Arthroplasty

Abstract: The demand for total knee arthroplasty (TKA) continues to grow exponentially, and this has been attributed to a higher prevalence of osteoarthritis and excellent procedural success. In particular, with increasing life expectancies and obesity rates, surgeons are seeing patients with a wider age range. Therefore, we assessed the effects of patient age on: (1) range of motion (ROM); (2) pain and function; (3) physical and mental status; and (4) activity levels following TKA. We assessed 278 TKA patients (108 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
(16 reference statements)
5
15
0
Order By: Relevance
“…This finding corroborates the literature in that, in the majority of studies, the relative frequency of women was higher than that of men. In the study by van Egmond, C et al 27 the relative frequency of women was 60%, a percentage similar to that of the Elmallah R et al study, 28 in which 61.1% of the patients were female, and of the study by Jauregui J et al, 29 which showed that 61.5% of the sample were female. Age is another factor that is actively related to the period after surgery, 28 being an important predictor of functional outcome.…”
Section: Eficácia Do Tratamento Adjuvante Da Dor Pós-artroplastia Totsupporting
confidence: 60%
See 1 more Smart Citation
“…This finding corroborates the literature in that, in the majority of studies, the relative frequency of women was higher than that of men. In the study by van Egmond, C et al 27 the relative frequency of women was 60%, a percentage similar to that of the Elmallah R et al study, 28 in which 61.1% of the patients were female, and of the study by Jauregui J et al, 29 which showed that 61.5% of the sample were female. Age is another factor that is actively related to the period after surgery, 28 being an important predictor of functional outcome.…”
Section: Eficácia Do Tratamento Adjuvante Da Dor Pós-artroplastia Totsupporting
confidence: 60%
“…In the study by van Egmond, C et al 27 the relative frequency of women was 60%, a percentage similar to that of the Elmallah R et al study, 28 in which 61.1% of the patients were female, and of the study by Jauregui J et al, 29 which showed that 61.5% of the sample were female. Age is another factor that is actively related to the period after surgery, 28 being an important predictor of functional outcome. 30 In the study, patients older than 70 years presented a relative frequency of 45.45% in the intervention group and 43.47% in the control group.…”
Section: Eficácia Do Tratamento Adjuvante Da Dor Pós-artroplastia Totsupporting
confidence: 60%
“…Geriatric patients have been shown to have a higher rate of intra- and postoperative complications and longer hospitalization [5, 6]. An age of 70 years or older is a predisposing factor for postoperative delirium [7], the incidence of which is up to 50% after orthopedic operations [8].…”
Section: Introductionmentioning
confidence: 99%
“…Up to 38% of quadriceps strength deficit has been reported in end stage osteoarthritis of the knee [9], while in geriatric patients with severe osteoarthritis this deficit is expected to be even larger. Altogether, patients above 80 years have been shown to have poorer general outcomes following arthroplasty [6]. Currently only 5% of all TKAs are performed in patients aged 85 years or older [5].…”
Section: Introductionmentioning
confidence: 99%
“…2 Outcome measures analyses have demonstrated worse outcomes on mental components, and are equivalent on pain and function for younger patients. 19 Understanding this relationship is important to create realistic postoperative expectations, a process which has been demonstrated to improve post-TKA outcomes. 20,21 Not meeting patient expectations prior to surgery has been shown to be a strong predictor of patient dissatisfaction after TKA.…”
mentioning
confidence: 99%